Investigations about new methods of library marketing in Chinese "985" Project Universities. Issue 6 (10th August 2015) - Hua, Xiaoqin; Si, Li; Zhuang, Xiaozhe; Xing, Wenming
Abstract : Purpose: – Under the new technological environment, academic libraries meet an extremely intense competition in offering information services, and marketing becomes an important means to attain the goal of their sustainable development. The purpose of this paper is to get an overview of library marketing in Chinese "985" Project Universities, the authors undertook a survey on each library of "985" Project Universities released on the web site of Ministry of Education of the People's Republic of China. And then the authors identified some successful practices based on the survey. Design/methodology/approach: – First, the content of each web site, along with the individual hyperlinks and categories that every library web site has, were browsed to check the availability of the categories. Second, the search function of each library was explored using terms like "blog, " "video" and "tutorial" to retrieve information about services. Third, the Google search engine was used to retrieve information from Renren, microblog and YouTube accounts combining with the name of each library. And then the authors consult reference librarians about marketing methods and tools applied in their libraries with real-time online reference services. Findings: – This paper suggests that 29 libraries are exploiting video marketing, which is the most widely used marketing methods, accounting for 74.36 percent. Mobile library marketing and microblog marketing are another two major application among the 39 "985" Project Universities libraries in China, respectively, accounting for 69.23 and 58.97 percent. Originality/value: – The paper reveals that there are some deficiencies lying in the marketing of these libraries: characteristic resources in really simple syndication (RSS) are insufficient, video themes turn to be traditional and plain, network media marketing is relatively uncommon, and mobile library marketing is limited to mobile messaging services. It may fill in the gap of better understanding the relationship between the traditional information services and modern services from users' perspective. It is instructive for libraries to systematically summarize success or failure experience of other library marketing, and keep an innovative concept and global vision.